Prostatic-Specific Antigen Levels in Men from Two Andean Cities of Peru - Alcantara-Zapata, Diana E. (2018)
Prostatic-specific antigen (PSA) is a biomarker that has been broadly used in aiding the diagnoses of benign prostatic hyperplasia (BPH) and prostate cancer. The incidence of both, which are, in part, androgen-driven diseases, has increased in men worldwide over the past 40 years.